Non-Invasive Brain Stimulation for the Treatment of Symptoms Following Traumatic Brain Injury - Dhaliwal, Simarjot K.; Meek, Benjamin P.; Modirrousta, Mandana M. (Frontiers in Psychiatry, 2015)
Background: Traumatic brain injury (TBI) is a common cause of physical, psychological, and cognitive impairment, but many current treatments for TBI are ineffective or produce adverse side effects. Non-invasive methods of brain stimulation could help ameliorate some common trauma-induced symptoms. Objective: This review summarizes instances in which repetitive Transcranial Magnetic Stimulation (rTMS) and transcranial Direct Current Stimulation (tDCS) have been used to treat symptoms following a traumatic brain injury. A subsequent discussion attempts to determine the value of these methods in light of their potential risks. Methods: The research databases of PubMed/MEDLINE and PsycINFO were electronically searched using terms relevant to the use of rTMS and tDCS as a tool to decrease symptoms in the context of rehabilitation post-TBI. Results: Eight case-studies and four multi-subject reports using rTMS and six multi-subject studies using tDCS were found. Two instances of seizure are discussed. Conclusions: There is evidence that rTMS can be an effective treatment option for some post-TBI symptoms such as depression, tinnitus, and neglect. Although the safety of this method remains uncertain, the use of rTMS in cases of mild-TBI without obvious structural damage may be justified. Evidence on the effectiveness of tDCS is mixed, highlighting the need for additional